Hybidization Studies in Okra (Abelmoschus spp (L.) Moench) - Amitaaba, T (University of Ghana, 2016)
Okra (Abelmoschus spp. L. Moench) is an important multi-purpose vegetable crop cultivated and consumed across all tropical and temperate regions of the world. In Ghana, it is popular in all ten regions and increasing quantities are exported to Europe in the fresh form. The crop has received little attention by way of breeding to produce varieties combining the most desirable qualities to boost local cultivation and export. Ten accessions of Abelmoschus spp., comprising two species, A. esculentus (T1, T2, T3, VT, ID and AG) and A. callei (KB, AM, YL and T4) collected from six geographical regions of Ghana were crossed in all possible combinations to assess inter-specific as well as intra-specific hybridisation between and within species. Reciprocal crosses were also carried out and the performances of their F1 offspring were evaluated against the respective parents for expression of heterosis for key quantitative traits including days to 50% germination, days to 50% flowering, plant height, fresh fruit weight, length of pod and number of seeds per pod. Genetic relatedness among the accessions and their progeny was established by way of a dendrogrom based on furthest neighbour method (Euclidean). All six accessions of Abelmoschus esculentus were able to hybridize with one another in both direct and reciprocal cross combinations with high degree of crossability index (CI) (45.71% to 90.32%). On the other hand, cross-compatibility among A. esculentus and A. callei was successful only in one direction when A. esculentus was used as females also with a CI between 34.48% and 60%. Parental lines T3 and T1 emerged as the most compatible female and male respectively. Crossability success was relatively high during early hours of the day but decreased continuously in subsequent hours. Ten parental accessions and 61 Fl progenies of A. esculentus and A.callei evaluated for 15 qualitative and 8 quantitative traits exhibited significant variations in all quantitative traits studied. Clustering pattern based on quantitative traits largely revealed no duplicates and clustering pattern especially among parental accessions, appears to reflect relationship based upon speciation as parental accessions belonging to A. caillei are clustered towards one end of the dendrogram, while members belonging to A. esculentus clustered towards the opposite end. Contributions of the three principal components were 45.98 %, 23.31 %, and 14.46% for the first (PC1), second (PC2) and third (PC3) respectively, with corresponding Eigen values of 3.21837, 1.63171 and 1.01212 respectively, cumulating into maximum of 83.75 % of total variance. These results demonstrate possibility of producing superior hybrids of okra through artificial cross-pollination. Key recommendations based on these findings include i) use of molecular markers to confirm results of morphological characterisation and also to better understand inheritance of qualitative traits. ii) Genes linked to agronomically important traits in okra should be genetically mapped through Quantitative Traits Loci (QTLs) to serve as a baseline data platform for researchers and breeders.iii) Further studies on inheritance of qualitative traits stretching to the F2 or even F3 generations should be carried out, preferably using molecular markers to fully understand the pattern of segregation with appropriate ratios.
Thesis (MPhil)
Keywords: Okra; Vegetable Crop; Tropical; Temperate